(untitled) (Research, Society and Development, 2021)
Residues from Home Health Services (RSSD) are all residues generated by users assisted in their homes, and even in small quantities, they are particularly important given the inadequate destination they receive. The objective of the study is to present a propositional manual for the implementation of the Home Health Service Management Plan (PGRSSD) for the RSSD generated in the health care of users attended in the homes of São Luís-MA. The methodology used quantified and identified the types of RSSD generated in home care to 113 patients, registered in the Best at Home Program of the Municipal Health Secretariat-SEMUS, and classify them according to the dangerousness and risks in handling, which involves since the generation stage until the final destination. The methodological assessment instruments were based on RDC 222/2018 and CONAMA resolutions 357/2005 and 358/2005 and Regulatory Norm NR 32 - Health and Safety at Work in Health Services. The results showed the importance of segregation and the appropriate final destination of these residues to avoid the direct risk to the teams that carry out the procedures, to the patients and to the companions. The manual with instructions for managing the RSSD was prepared with suggestions for a proposal for a PGRSSD.